Accumulation of di(2‐ethylhexyl) phthalate causes endocrine‐disruptive effects in marine medaka (Oryzias melastigma) embryos. Issue 1 (28th July 2014) - Ye, Ting; Kang, Mei; Huang, Qiansheng; Fang, Chao; Chen, Yajie; Liu, Liangpo; Dong, Sijun
ABSTRACT: Di (2‐ethylhexyl) phthalate (DEHP) is extensively distributed in marine environments. However, limited research on the toxicological and molecular effects of DEHP on marine organisms has been conducted. Our study investigated the accumulation, elimination, and endocrine‐disruptive effects of DEHP on embryonic marine medaka ( Oryzias melastigma ). The medaka embryos were continuously exposed to DEHP (0.01, 0.1, and 1 mg/L) or 17β‐estradiol (E2, 0.01 mg/L) until hatching, and the newly hatched larvae were then transferred to clean sea water for 12 days of depuration. DEHP and E2 appeared to have no significant effects on the mortality and hatching rates of medaka embryos, but E2 exposure significantly delayed the hatching. Significantly higher DEHP embryonic burdens were detected in the group treated with higher DEHP (0.1 and 1 mg/L) at 10 dpf (days post fertilization). The recovered larvae showed an elimination tendency of DEHP during the recovery period. DEHP had no significant effects on the transcriptional responses of endocrine‐disrupting biomarker genes in the 3‐dpf embryos. Treatment with 0.1 and 1 mg/L DEHP elicited a significant induction of transcriptional responses of ER, PPAR, and the CYP19 genes in a concentration‐dependent manner at 10 dpf, indicating endocrine disruption may be due to bioaccumulation of DEHP. With the elimination of DEHP during the depuration period, all of the effects on these genes showed no significant effects. However, 0.1 mg/L E2 significantly affected the expression of ER, PPAR, and the CYP19 genes in the exposed embryos at both 3 and 10 dpf and recovered larvae. Therefore, these results demonstrate that accumulation of DEHP caused endocrine disruption in medaka embryos and that recovery in clean sea water may weaken the endocrine‐disrupting effects. © 2014 Wiley Periodicals, Inc. Environ Toxicol 31: 116–127, 2016.